Inhibition of the Interaction Between Group I Metabotropic Glutamate Receptors and PDZ-Domain Proteins Prevents Hippocampal Long-Term Depression, but Not Long-Term Potentiation - Neyman, Sergey; Braunewell, Karl-Heinz; O’Connell, Kara E.; Dev, Kumlesh K.; Manahan-Vaughan, Denise (Frontiers in Synaptic Neuroscience, 2019)
The group I metabotropic glutamate (mGlu) receptor subtypes, mGlu1 and mGlu5, strongly regulate hippocampal synaptic plasticity. Both harbour PDZ (PSD-95/discs-large/ ZO-1) motifs at their extreme carboxyl terminals, which allow interaction with the PDZ domain of Tamalin, regulate the cell surface expression of group I mGlu receptors, and may modulate their coupling to signalling proteins. We investigated the functional role of this interaction in hippocampal long-term depression (LTD). Acute intracerebral treatment of adult rats with a cell permeable PDZ-blocking peptide (pep-mGluR-STL), designed to competitively inhibit the interaction between Tamalin and group 1 mGlu receptors, prevented expression of LTD in the hippocampal CA1 region without affecting long-term potentiation or basal synaptic transmission. Pep-mGluR-STL prevented facilitation by the group I mGlu receptor agonist, DHPG, and the mGlu5 agonist, CHPG, of short-term depression into LTD, suggesting that Tamalin preferentially acts by mediating signalling through mGlu5. These data support that Tamalin is essential for the persistent expression of LTD and that Tamalin subserves the effective signalling of group 1 mGlu receptors.